2015
DOI: 10.1539/joh.14-0201-oa
|View full text |Cite
|
Sign up to set email alerts
|

Job characteristics and musculoskeletal pain among shift workers of a poultry processing plant in Southern Brazil

Abstract: workers, such as changing positions frequently during work and implementation of rest breaks and a workplace exercise program, so as to improve worker quality of life. (J Occup Health 2015; 57: 448-456)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…Musculoskeletal Disorder is a health problem involving the joints, muscles, tendons, skeleton, cartilage, ligaments, and nerves (Van et al, 2016). Musculoskeletal Disorder is related to the intensity and severity of work, although often light activities such as housework or exercise may also be involved (Barro et al, 2015). Some studies show that MSDs can occur due to a combination of various factors.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal Disorder is a health problem involving the joints, muscles, tendons, skeleton, cartilage, ligaments, and nerves (Van et al, 2016). Musculoskeletal Disorder is related to the intensity and severity of work, although often light activities such as housework or exercise may also be involved (Barro et al, 2015). Some studies show that MSDs can occur due to a combination of various factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies have investigated the impact of these risks indicators on lower limb pain. A recent study found a significant association of lower limb pain with extreme temperatures and night shifts among workers of a processing plant (Barro et al 2015 ). Performing repetitive tasks may increase the prevalence of MSDs such as upper extremity pain and low back pain (Andersen et al 2007 ; Latza et al 2002 ; Roelen et al 2008 ; Tissot et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shift work and the resulting misalignment of sleep schedules with the circadian rhythm have been associated with a myriad of adverse health conditions, including increased rates of obesity, cardiac disease and cancer [8,18]. Additionally, shift work has been correlated with increased rates of reported musculoskeletal and lower back pain [17,15,1]. We simulated an 8-h shift work schedule between 11 pm and 7 am for 5 consecutive days as may occur for a typical shiftwork week (Figure 4).…”
Section: Pain Sensitivity Under Shift Work Schedulesmentioning
confidence: 99%